2022
DOI: 10.1039/d2nj02052a
|View full text |Cite
|
Sign up to set email alerts
|

Single-component, metal-free, solvent-free HO-functionalized 1,2,3-triazole-based ionic liquid catalysts for efficient CO2 conversion

Abstract: A series of HO-functionalized 1,2,3-triazolic ionic liquids (1-9b) bearing different alkyl chains and counter-anions were evaluated as green, single component bifunctional catalysts for the cycloaddition reaction of CO2 and epoxides....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…[21][22][23] These compounds have shown their ability to be used as polar aprotic solvents in chemical processes 24,25 and as electrolyte solvents in lithium-ion batteries. 26,27 It is relevant to point out that a large number of catalyst systems, such as metal-salen complexes, [28][29][30][31][32][33][34][35][36][37][38] metal organic frameworks [39][40][41][42] and ionic liquids, [43][44][45] have been recently prepared to carry out the synthesis of cyclic carbonates with excellent yields and selectivities. However, the multistep preparation, meticulous purification, and the elevated price associated with the synthesis of most metal-based catalysts could be the bottlenecks of their largescale production, which make it desirable to develop metal-free catalysts or organocatalysts to perform the cyclic carbonate production.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] These compounds have shown their ability to be used as polar aprotic solvents in chemical processes 24,25 and as electrolyte solvents in lithium-ion batteries. 26,27 It is relevant to point out that a large number of catalyst systems, such as metal-salen complexes, [28][29][30][31][32][33][34][35][36][37][38] metal organic frameworks [39][40][41][42] and ionic liquids, [43][44][45] have been recently prepared to carry out the synthesis of cyclic carbonates with excellent yields and selectivities. However, the multistep preparation, meticulous purification, and the elevated price associated with the synthesis of most metal-based catalysts could be the bottlenecks of their largescale production, which make it desirable to develop metal-free catalysts or organocatalysts to perform the cyclic carbonate production.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous catalytic systems are relatively superior to homogeneous ones with regard to chemical and thermal stability, easy separation, and good recyclability. Over the past 10 years, several heterogeneous materials such as porous organic polymers, [29][30][31] nitrogen-doped porous carbon monoliths, 32 modified molecular sieves, 33,34 ion-exchange resins, 35 nanoparticles, 36 metal oxides, 37 hydroxyl-functionalized ionic liquids, 38,39 metal organic frameworks, [40][41][42] poly(ionic liquid), 43,44 and supported catalysts [45][46][47][48][49][50][51][52] have been developed as efficient catalysts. Recently, porous polymers possessing the advantages of porous materials as well as polymer materials have been gaining immense research interest due to tunable pore size, diversity of structures and a broad range of applications especially in the field of pollutant removal, 53,54 gas separation and storage, [55][56][57][58] energy storage and chemical catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Among all these catalysts, ionic liquids are widely used for their excellent property which could be designed the structures for applications in the fields of CO 2 capture, conversion, and storage, [10] for example, Chen et al [10d] . reported that amino acid ionic liquids showed better CO 2 absorption efficiency when their concentrations were 40 wt% or 50 wt% at 293 K to 313 K. Á. F. Arruda et al [10e] . designed the attractive potential of hydroxyl functionalized 1,2,3‐triazole‐based ionic liquid catalysts for efficient CO 2 conversion to cyclic carbonates.…”
Section: Introductionmentioning
confidence: 99%